Implementation of 25 Basic Skills of Great Surabaya Cadres (KSH) in Supporting The Implementation of Family Posyandu in The Working Area of The Mojo Public Health Center - Maya Putri Nabilah Hisanah; Pulung Siswantara (Jurnal Pengabdian Ilmu Kesehatan, 2026)
The implementation of Family Integrated Health Posts ( Posyandu Family ) as part of Primary Health Care Integration requires community health volunteers to master comprehensive competencies across the life cycle approach. In Surabaya, this role is carried out by Kader Surabaya Besar (KSH), who supports community-based primary health services. This internship report aims to describe the implementation of the 25 basic competencies of KSH in supporting Family Posyandu activities in the working area of Puskesmas Mojo. The internship was conducted for nine weeks using observation, discussion, and document review methods. Primary data were obtained through direct observation of Family Posyandu activities and discussions with cadres, while secondary data were collected from institutional reports and administrative records. Problem prioritization was analyzed using the Urgency, Seriousness, and Growth (USG) method, followed by root cause analysis using a fishbone diagram and alternative solution assessment using the MEER method. The results showed that although the 25 basic competencies had been implemented, their mastery among cadres remained uneven due to phased training, workload expansion, and dense service flow. Strengthening capacity-building efforts and practical supporting tools are necessary to optimize cadre performance.